Case Report: Selexipag in pediatric pulmonary hypertension: Initiation, transition, and titration - Faircloth, Jenna M.; Bhatt, Neelam D.; Chartan, Corey A.; Coleman, Ryan D.; Villafranco, Natalie; Ruiz, Fadel E.; Morales-Demori, Raysa; Whalen, Elise; Ely, Erin; Fombin, Rozmeen; Varghese, Nidhy P. (Frontiers in Pediatrics, 2023)
Selexipag, a selective prostacyclin receptor agonist, is approved for the treatment of pulmonary arterial hypertension in WHO Group 1 adult patients. Compared to parenteral prostacyclin formulations, selexipag is considered to offer significant improvement in patient and caregiver quality of life because of its oral formulation, frequency of administration and mechanism of action. Although experience in the pediatric population is limited to case reports in older adolescent patients and selexipag is not approved for use in the pediatric pulmonary hypertension population, many pediatric centers are expanding use of this therapy to this population. We report our institution’s experience in the use of selexipag to treatment pulmonary hypertension in children less than 10 years of age, between 10 – 30 kg. Seven patients were initiated on selexipag therapy including de novo initiation and transition from intravenous treprostinil to oral selexipag. All patients were on stable background therapy with phosphodiesterase-5 inhibitor and endothelin receptor antagonist therapies at baseline. All patients reached their planned goal selexipag dose during admission without need for changes to titration schedule and without hemodynamic deterioration. In our experience, oral selexipag is safe and well-tolerated in young pediatric patients with pulmonary hypertension. Based on our favorable experience, we developed an institution-specific selexipag process algorithm for continued successful use in the pediatric population.